EFEKTIVITAS PEMUNGUTAN RETRIBUSI IJIN MENDIRIKAN BANGUNAN PADA BADAN PENANAMAN MODAL DAN PELAYANAN PERIJINAN KABUPATEN NGAWI - Aris Tri Haryanto, Sangrila Puspita Dewi & (JI@P, 2016)
Effectiveness of Tax Collection of Building Construction Permission at theCapital Investment And Permission Service Agency in Ngawi Regency.This research aimed to describe the effectiveness of tax collection forbuilding construction permissin at Capital Investment and PermissionService in Ngawi Regency. Case study research method was employed inconducting the research. Primary data sources derived from interviewand obseravation results. On the other hand, secondary data wascollected from the documents, reports, and notes. This research fndingwas described in narrative way. Research result showed that the taxcollection for the permission for building reconstruction was less effective.This due to the low of responsiveness of the employees, since some ofthe oemployees were the contracted employees who were lack inunderstanding the importance of tax for building reconstructionpermission. The low effectiveness was also seriously caused by thedamages and the limited equipments which in turn, to hamper the taxcollection process. On the other hand, however, research result indicatedthat service efficiency, procedures of servce, ordinates and subordinatescoordination were found effective.Key words: responsiveness, tax collection, effiiciency, effectiveness.